Beyond Preconditioning: Postconditioning as an Alternative Technique in the Prevention of Liver Ischemia-Reperfusion Injury. (2nd June 2016) - Theodoraki, Kassiani; Karmaniolou, Iosifina; Tympa, Aliki; Tasoulis, Marios-Konstantinos; Nastos, Constantinos; Vassiliou, Ioannis; Arkadopoulos, Nikolaos; Smyrniotis, Vassilios
Abstract : Liver ischemia/reperfusion injury may significantly compromise hepatic postoperative function. Various hepatoprotective methods have been improvised, aiming at attenuating IR injury. With ischemic preconditioning (IPC), the liver is conditioned with a brief ischemic period followed by reperfusion, prior to sustained ischemia. Ischemic postconditioning (IPostC), consisting of intermittent sequential interruptions of blood flow in the early phase of reperfusion, seems to be a more feasible alternative than IPC, since the onset of reperfusion is more predictable. Regarding the potential mechanisms involved, it has been postulated that the slow intermittent oxygenation through controlled reperfusion decreases the burst production of oxygen free radicals, increases antioxidant activity, suppresses neutrophil accumulation, and modulates the apoptotic cascade. Additionally, favorable effects on mitochondrial ultrastructure and function, and upregulation of the cytoprotective properties of nitric oxide, leading to preservation of sinusoidal structure and maintenance of blood flow through the hepatic circulation could also underlie the protection afforded by postconditioning. Clinical studies are required to show whether biochemical and histological improvements afforded by the reperfusion/reocclusion cycles of postconditioning during early reperfusion can be translated to a substantial clinical benefit in liver resection and transplantation settings or to highlight more aspects of its molecular mechanisms.